2014
DOI: 10.3210/fst.33.1
|View full text |Cite
|
Sign up to set email alerts
|

Façade Tests on Fire Propagation along Combustible Exterior Wall Systems

Abstract: With regard to fire protection for exterior walls of a building, only fire-resistive performance is considered, according to the current building standard law of Japan. In previous authors' studies, a new test method for evaluation of fire propagation along combustible cladding was proposed using primarily test specimens of façade walls with exterior thermal insulation without vent layers. In this paper, newly made results of façade fire tests also with other specimens of combustible facades, such as sandwich … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 3 publications
1
12
0
Order By: Relevance
“…Fire behavior of EPS with sandwich panel structure is characterized by using large‐scale room fire tests according to the ISO 9705 or ISO 13784‐1 protocols. In our previous large‐scale fire investigation, test method for evaluation of fire propagation along combustible exterior wall systems was set up and tested . As for the opening edge treatment method, it is believed to be critical to alleviate or inhibit a vertical flame spreading.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fire behavior of EPS with sandwich panel structure is characterized by using large‐scale room fire tests according to the ISO 9705 or ISO 13784‐1 protocols. In our previous large‐scale fire investigation, test method for evaluation of fire propagation along combustible exterior wall systems was set up and tested . As for the opening edge treatment method, it is believed to be critical to alleviate or inhibit a vertical flame spreading.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous large-scale fire investigation, test method for evaluation of fire propagation along combustible exterior wall systems was set up 14 and tested. [15][16][17] As for the opening edge treatment method, it is believed to be critical to alleviate or inhibit a vertical flame spreading. Currently, although it is clear that EPS ETICS reaction-to-fire performance will show a complex reaction-to-fire performance in a fire because of EPS tendency to melt and drip, little knowledge of relationship between EPS ETICS reaction-tofire performance and opening edge treatment, heating intensity, and EPS burn area is available.…”
Section: Introductionmentioning
confidence: 99%
“…Under these circumstances, this study aims to discuss a method to evaluate the reaction-to-fire performance of fire-retardant-treated wood used as building facades with aging deterioration taken into consideration. To be specific, a building facade fire-spread test in Japan (JIS A 1310) [4,5] and cone calorimeter test (ISO 5660-1) [6] were conducted on specimens that had undergone an accelerated weathering test so as to compare their performance and make fundamental reviews.…”
Section: Introductionmentioning
confidence: 99%
“…However, installation of combustible material over the exterior wall could cause largescale fire propagation. In previous studies of authors, façade test method for evaluation of fire propagation over combustible cladding was proposed, using various types of combustible façade specimens [1,2]. Heat output of gas burner in a combustion chamber was set 600 kW, because temperature in the chamber was about 1000 • C and temperature at lintel was about 900 • C, which are near at real fire condition.…”
Section: Introductionmentioning
confidence: 99%
“…Actual fire incidents in the world have shown that massive façade fire could occur at the exterior side of building wall even when the wall itself is fire resistant. In previous studies of the authors, a test method of façade fire was proposed for evaluating the vertical fire propagation over an external wall within the same building [1,2]. Based on these studies, new domestic standard test method was established in Japan as JIS A 1310: 2015, "Test method for fire propagation over building façades" at the end of January 2015 [3].…”
mentioning
confidence: 99%